A miRNA-HERC4 pathway promotes breast tumorigenesis by inactivating tumor suppressor LATS1. Issue 8 (1st February 2019) - Xu, Youqin; Ji, Kaiyuan; Wu, Meng; Hao, Bingtao; Yao, Kai-tai; Xu, Yang
Abstracts: The E3 ligase HERC4 is overexpressed in human breast cancer and its expression levels correlated with the prognosis of breast cancer patients. However, the roles of HERC4 in mammary tumorigenesis remain unclear. Here we demonstrate that the knockdown of HERC4 in human breast cancer cells dramatically suppressed their proliferation, survival, migration, and tumor growth in vivo, while the overexpression of HERC4 promoted their aggressive tumorigenic activities. HERC4 is a new E3 ligase for the tumor suppressor LATS1 and destabilizes LATS1 by promoting the ubiquitination of LATS1. miRNA-136-5p and miRNA-1285-5p, expression of which is decreased in human breast cancers and is inversely correlated with the prognosis of breast cancer patients, are directly involved in suppressing the expression of HERC4. In summary, we discover a miRNA-HERC4-LATS1 pathway that plays important roles in the pathogenesis of breast cancer and represents new therapeutic targets for human breast cancer.